Integrative reconstruction of cancer genome karyotypes using InfoGenomeR - Yeonghun Lee (Nature Portfolio, 2021)
Karyotyping of cancer genomes at the base-level is technically challenging. Here, the authors introduce InfoGenomeR, an algorithm that can infer cancer genome karyotypes from whole-genome sequencing data, and test their model on breast, ovarian and brain cancer samples; and identify private and shared mutations between primary and metastatic cancer samples.